Technology features of decellularization of human liver fragments as tissue-specific fine-grained matrix for cell-engineering liver construction - E. A. Nemets; L. A. Kirsanova; Ju. B. Basok; M. Ju. Schagidulin; E. A. Volkova; S. T. Metelsky; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
One of the problems when you create a bioengineered liver, as an alternative to transplantation of the donor liver in the treatment of end-stage liver failure, is the matrix, able to temporarily perform the functions of the natural extracellular matrix (ECM) and provide the necessary conditions to maintain the viability of the liver cells. The main disadvantage of resorbable biopolymer matrices is the absence of tissue speciﬁ c properties and the impossibility of reproducing the unique structure of the ECM of the liver.Aim: to develop technology for decellularization of liver tissue fragments, saving the structural properties of native ECM of the liver.Materials and methods. The decellularization of mechanically grinded human liver fragments was carried out in three changes of buffer solution (pH = 7.4) containing 0.1% sodium dodecyl sulfate and increasing the concentration of Triton X100 (1%, 2% and 3%, respectively). During technology development were investigated the effects of duration, conditions (static, dynamic, rotary system, magnetic stirrer) washing and methods of liver tissue grinding on the completeness of removal of cellular elements and detritus preserving the the liver ECM structure. Slices of decellularized liver tissue samples were stained by hematoxylin and eosin, and Masson method for the detection of connective-tissue elements.Results. Histological analysis methods showed that the best from the point of view of efﬁ ciency of decellularization and the safety of the structure of own human liver ECM, is a mode of washing of liver fragments for three days at room temperature in static conditions, accompanied by stirring by a magnetic stirrer for 2–3 times a day for one hour. Longer time or a large multiplicity of mixing mode is accompanied by increased risk of liver tissue damage. On the basis of the experimental results obtained the algorithm of preliminary study of donor human liver designed to optimize the process of obtaining decellularization fragments of liver tissue was elaborated.Conclusion. It was elaborated the algorithm and technology of obtaining of decellularized liver tissue fragments from the human donor liver which saved the structural properties of native ECM of the liver and complete removal of cellular elements and detritus.